PEMBERDAYAAN PARTISIPATIF MELALUI INOVASI PUPUK ORGANIK CAIR LIMBAH SALAK DI DESA GARUNGLOR - Arya Pratama, Ryandito; Syamsidh Dhuha, Wildan Faza; Syamsiyah, Dalfa; Safitri, Eka Wening; Husna Raudhah, Lailli Brillianta; Priscilia, Meytha; Putri, Nindia Kusuma; Cahyaningtyas, Wening; Proborini, Alethea Laksmita; Muslim, Fakhri (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2026)
The Community Service Program (Kuliah Kerja Nyata/KKN) conducted by Universitas Sebelas Maret Group 173 in Garunglor Village, Sukoharjo District, Wonosobo Regency, was implemented in response to issues related to salak (snake fruit) waste management and the dominant use of chemical fertilizers in local agricultural practices. Salak fruits that do not meet market standards are generally discarded without processing, leading to production inefficiency and potential agroecosystem disturbances. This topic was selected due to the importance of optimizing local resources and promoting environmentally sustainable farming practices. The program applied a participatory approach based on Participatory Rural Appraisal (PRA), involving observation, interviews, socialization sessions, and hands-on training in the production of liquid organic fertilizer (LOF) derived from salak waste. The results indicate increased community understanding and a shift in perception of waste as a productive agricultural input. Ecologically, the initiative supports nutrient cycling and soil quality improvement, while economically contributing to production cost efficiency. Therefore, the utilization of salak waste into liquid organic fertilizer represents a strategic step toward a more circular, adaptive, and sustainable local agricultural system.